Effects of thermal treatment on the complex structure of luminescence emission of Li-doped ZnO screen-printed films - Chukova, O.; Borkovska, L.; Khomenkova, L.; Korsunska, N.; Ponomaryov, S.; Androulidaki, M.; Stratakis, E. (Frontiers in Physics, 2023)
The ZnO-Li films were synthesized and investigated in a search of the RE-free phosphor materials capable of emitting intense visible light in a wide spectral range. The effects of the both of hetero-valent doping with lithium and high-temperature annealing on the optical properties of ZnO films were studied. The films were prepared by screen-printing method on Al2O3 substrate and annealed at 800 – 1000 oC during 0.5-3 h in the air. Both the doping and annealing are found to result in the transformation of the shape of reflectance spectra over the 300 – 400 nm range and shift of the absorption edge to long-wavelength region. At the same time, the bandgap value estimated taking into account exciton peak position and its binding energy is found to be independent of the Li doping. The feature at 300-400 nm and shift of absorption edge are ascribed to the appearance of absorption band excited the yellow PL band. The photoluminescence spectra of undoped and Li-doped films show the emission bands in the ultraviolet and visible spectral ranges. The ultraviolet emission is caused by ZnO exciton recombination. The visible emission band consists of several components peaked at 430, 482, 540, 575 and 640 nm. Their relative intensities depend on Li doping, annealing temperature and annealing duration. The 430 and 482 nm luminescence bands are observed in Li-doped films only. Their excitation spectra show the peak at 330-340 nm which energy significantly exceeds the ZnO bandgap energy. Consequently, the 430 and 482 nm luminescence bands are attributed to an additional crystal phase formed under annealing. Other components of visible emission band are ascribed to the defect-related emission of ZnO. The possible nature of these bands is discussed. The Li doping and annealing at intermediated temperatures results in the appearance of blue emission and an enhancement of other visible bands that makes the ZnO-Li films a perspective material for photonic applications.